Pengaruh Kepuasan Kerja Terhadap Kinerja Pegawai Pada Dinas Kependudukan Dan Catatan Sipil Kota Makassar - Anastasya Cahyana Waode; Buyung Romadhoni; Sri Andayaningsih (Pusat Riset dan Inovasi Nasional, 2025)
This research is a type of quantitative research with the aim of determining the Influence of Job Satisfaction on Employee Performance at the Population and Civil Registration Service of Makassar City with a population of 156 employees and a sample of 113 employees. The type of data used in this study is quantitative data obtained from questionnaires that are distributed and related to the problem being studied. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study uses the Likert Scale method. Based on the results of data research using statistical calculations through the Statistical Package For the Social Science (SPSS) version 27 application regarding the Influence of Job Satisfaction on Employee Performance at the Population and Civil Registration Service of Makassar City which has been discussed in the previous chapter, the author draws an important conclusion job satisfaction has a positive and significant effect on employee performance at the Population and Civil Registration Service of Makassar City. This is shown from the results of the calculation, namely the regression coefficient value of 0.405 and the significant value below 0.05, which is 0.000.